Changes in symptom content from a clinical high‐risk state to conversion to psychosis. Issue 2 (3rd August 2017) - Marshall, Catherine; Lu, Yun; Lyngberg, Kristina; Deighton, Stephanie; Cadenhead, Kristin S.; Cannon, Tyrone D.; Cornblatt, Barbara A.; McGlashan, Thomas H.; Perkins, Diana O.; Seidman, Larry J.; Tsuang, Ming T.; Walker, Elaine F.; et al.
Abstract : Aim: There is an interest in the transition to psychosis for those at clinical high risk of developing psychosis. This transition is typically determined by a change in severity of the attenuated symptoms as they reach a psychotic level. However, any concomitant change in the content of such symptoms has not been examined. The current study aimed to examine potential qualitative changes in the symptom content from a clinical high‐risk state to a first episode of psychosis. Methods: Sixty‐seven individuals, who had been identified as meeting the attenuated psychotic syndrome based on the Structured Interview of Psychosis‐Risk Syndromes and who later developed a full‐blown psychosis were included in the study. Comprehensive clinical vignettes were written and raters were trained using the Content of Attenuated Psychotic Symptoms codebook to code for the presence of specific symptom content found within the attenuated psychotic symptoms of unusual thought content, suspicious ideas, grandiose ideas and perceptual abnormalities. Results: Two main changes in symptom content from baseline to conversion were observed. First, content that was vague and lacked intensity progressed to being more specific, concrete and severe. Second, new symptoms appeared whose onset occurred for the first time at conversion. Conclusion: A change in symptom content should be monitored by clinicians, as changes in content may be indications of a possible transition to psychosis.